Digital media practices in households kinship through data - Hjorth, Larissa 1971-; Ohashi, Kana; Sinanan, Jolynna; Horst, Heather A.; Pink, Sarah 1966-; Kato, Fumitoshi; Zhou, Baohua (Amsterdam University Press, 2020)
How are intergenerational relationships playing out in the digital rhythms of the household? Through extensive fieldwork in Tokyo, Shanghai and Melbourne, this book ethnographically explores how households are being understood, articulated and defined by digital media practices. It explores the rise of self-tracking, quantified self and informal practices of care at distance as part of contemporary household dynamics
Keywords: Haushalt; Medienkonsum